СПОСОБИ І ФОРМУЛА ТЛУМАЧЕННЯ ЦИВІЛЬНО-ПРАВОВИХ ДОГОВОРІВ - Антошкіна, Валерія Костянтинівна (SUPREMANCE OF LAW, 2018)
Defines the purpose, objectives and features of the interpretation of civil contracts. The features of application of methods of interpretation for treaties and examples from civil law and litigation. Researched formula interpretation according to Ukrainian law and in the legal framework of foreign countries.